Project management, orientation for decision makers - Dingle, John. (London Butterworth-Heinemann, 1997)
Effective policy making is one of the keys to the success of any project and in Project Management John Dingle examines and discusses the factors in this decision-making process that influence the outcome of the project. Dealing first with projects in the context of business risk, the author then explores investments and the management of risk through financial and contractual arrangements. Project management techniques are covered later in the text and the author focuses on the attitudes to management and project 'culture' which, when appropriately chosen and diligently applied, lead to effective project leadership. Based on the author's extensive experience in the petrochemical and related industries, and unique in its focus on project policy making and leadership, 'Project Management' provides an invaluable insight into the key factors that influence the success, or failure of any project, over and above the remit of practical management. It will prove compulsory reading for anyone involved in project planning and management. Structured through clearly identifiable sections Concerned with mindsets and attitudes to project management Focuses on projects as part of business risk, project investment and the management of risk, tools of the tradeof a project manager.
Keywords: management -- Project management -- decicion maker